Beyond physical boundaries: the impact of digital rendering on spatial identity - Entezarinajafabadi, Ali; Roig, Eduardo (Journal of Architecture and Urbanism, 2023)
This research investigates the concept of spatial identity by examining its definitions and Plato’s Allegory of the Cave, as well as Michel Foucault’s concept of heterotopia, to explore the relationship between the physical and digital worlds. To analyze the concept of spatial digital identity, we conducted a literature review of academic articles and case studies that focus on the intersection of digital technology and spatial identity. Using a thematic approach, we identified key themes regarding the influence of digital technology on physical spaces and its impact on spatial identity. Through a case study of Times Square, we examined the role of the digital world in shaping spatial identity, paying particular attention to the impact of urban screens, social media, online interactions, and digital applications. The study highlights the importance of considering the digital world in the planning, design, and use of public spaces, as it plays a critical role in shaping their spatial identity. Finally, the research highlights the importance of being aware of the impact of the digital world on spatial identity in order to develop a comprehensive and integrated approach to the design of public spaces in the contemporary world.